Struktur komunitas mikroartropoda tanah di lahan pertanian kentang di Desa Sembungan Dataran Tinggi Dieng, Jawa Tengah - Insan Shiddiq; Rully Rahadian; Udi Tarwotjo (Jurnal Biologi Tropika, 2020)
The use of manure in the area of  Dieng Plateau is likely to increase from year to year. Excessive use of fertilizer has the potential to disturb soil fauna. The objective of  this research are to know the effect of intensively use of pure chicken manure and chicken manure in combination with husk in the Dieng Plateau potato farm, Sembungan Village to structure of soil microarthropods. Sampling was located in two station of potatoes farmland that uses pure chicken manure (chicken manure: CM) and chicken manure in combination with husk (chicken manure + husk :CMS). Soil sampling was applied using transect line method with five sampling points. The structure of soil microarthropods communities was analysed into relative abundance, the Shannon-Wiener’s diversity index, the evenness index, the Sorensen’s similarity index, and Hutcheson’s t-test. The results showed that the density of soil microarthropods on potato farmland using chicken manure in combination with husk (5620 individuals/m2) was higher than farmland using pure chicken manure (1830 individual/m2). The dominant taxa in both farmland are Acari and Collembola. Based on the index of Sorensen similarities, the composition of soil microarthropods in both farmlands is relatively similar (76%). Statistically, the diversity of soil microarthropods between the two different potatoes farmland is significantly different.